2001
DOI: 10.1074/jbc.m101114200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Incorporation and Removal of Antiviral Deoxynucleotides by Human DNA Polymerase γ

Abstract: Mitochondrial toxicity can result from antiviral nucleotide analog therapy used to control human immunodeficiency virus type 1 infection. We evaluated the ability of such analogs to inhibit DNA synthesis by the human mitochondrial DNA polymerase (pol ␥) by comparing the insertion and exonucleolytic removal of six antiviral nucleotide analogs. Apparent steady-state K m and k cat values for insertion of 2,3-dideoxy-TTP (ddTTP), 3-azido-TTP (AZT-TP), 2,3-dideoxy-CTP (ddCTP), 2,3-didehydro-TTP (D4T-TP), (-)-2,3-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
183
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(189 citation statements)
references
References 58 publications
6
183
0
Order By: Relevance
“…17 The DNC TG here offered an approach to evaluate NRTI toxicity in vivo and linked NRTI toxicity to mitochondrial import and nucleotide homeostasis. 4 For some time, our group [26][27][28] and others [29][30][31][32][33][34][35] have studied mechanisms of mitochondrial toxicity of NRTIs focusing on inhibition of DNA pol g (reviewed in Kaguni 36 ). NRTIs are firmly linked to altered mtDNA replication 10,37,38 through the DNA pol g hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 The DNC TG here offered an approach to evaluate NRTI toxicity in vivo and linked NRTI toxicity to mitochondrial import and nucleotide homeostasis. 4 For some time, our group [26][27][28] and others [29][30][31][32][33][34][35] have studied mechanisms of mitochondrial toxicity of NRTIs focusing on inhibition of DNA pol g (reviewed in Kaguni 36 ). NRTIs are firmly linked to altered mtDNA replication 10,37,38 through the DNA pol g hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…These toxicities are believed to be mediated through mitochondrial damage and are associated with mitochondrial DNA depletion [15][16][17]. The current prevailing hypothesis for this damage is by 3′-azido-3′-deoxythymidine-5′-triphosphate (AZTTP) inhibition of the mitochondrial DNA polymerase γ [18].…”
Section: Introductionmentioning
confidence: 99%
“…The current prevailing hypothesis for this damage is by 3′-azido-3′-deoxythymidine-5′-triphosphate (AZTTP) inhibition of the mitochondrial DNA polymerase γ [18]. However, several groups have demonstrated that relative to other nucleoside analog triphosphates, AZTTP is not a very good inhibitor of polymerase γ (50% inhibitory concentration (IC 50 ) of 100-200 μM AZTTP) [16,17,19]. Further, because 3′-azido-3′-deoxythymidine-5′-monophosphate (AZTMP) is a poor substrate for the cytosolic thymidylate kinase [20,21], levels of AZTTP high enough to inhibit polymerase γ have not been reported even in mitotic tissue [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Human DNA pol-␥ is inhibited by 50% with 20 M AZT triphosphate in a reverse transcriptase assay (Lim and Copeland, 2001). Gray et al (1995) showed that Hela cell DNA pol-␥ incorporated 3TC triphosphate nearly as well as ddC triphosphate into DNA.…”
Section: Lewis Et Almentioning
confidence: 99%
“…Human DNA pol-␥ removes chain terminators poorly compared with normal nucleotides. AZTmonophosphate is the most persistent chain terminator to DNA pol-␥ exonuclease activity (Lim and Copeland, 2001). It is possible that this could be significant mechanistically in the observed mitochondrial toxicity of DNA by AZT and related NRTIs.…”
Section: Nrti Pharmacological Classificationmentioning
confidence: 99%